A Generic Word in the Noble Qur'an - Andri Purwanto (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
This research discusses some problems and strategies in dealing with Islamic terms in the Noble Qur’an of English Translation of the Meanings and Commentary. This research shows how the professional translators annotated some Islamic terms according to the 5 general translation strategies. There are 75 terms that are studied and categorized according to the strategy and theory of translation, i.e. (1) A generic word with form; (2) A generic word with function; (3) A generic word with both form and function; (4) A generic word with comparison; (5) A generic word with a decriptive phrase.